An updated assessment of Ireland's wave energy resource using satellite data assimilation and a revised wave period ratio. (November 2020) - O'Connell, Ross; de Montera, Louis; Peters, Jared L.; Horion, Stéphanie
Abstract: Although wave energy harnessing is still at the pre-commercial stage, accurate and up-to-date resource assessments are necessary to the development of a wave energy industry. Radar altimeters aboard spaceborne platforms provide extensive spatial coverage of wave height estimations but cannot compensate for the scarcity of in-situ measurements associated with their poor temporal resolution. Ireland's wave energy resource is assessed here using a numerical model developed by Météo-France assimilating wave height data measured from satellite altimeters. The accuracy of the model is first assessed against in-situ wave buoy measurements and compared with other models that do not assimilate remotely sensed data. The use of satellite data assimilation appears to reduce the significant wave height error by 6 cm on average. A bespoke wave period ratio between the energy period and the up-cross period based on the experimental work of Cahill and Lewis (2014) is then used to compute the wave power around Ireland. The new map is compared with assessments which used other data and methodologies and is found to exhibit previously unidentified patterns as well as a substantial average wave power increase of approximately 20% in most areas and up to 30% in a region off the northwest coast. Highlights: Significant wave height bias reduced by at least 6 cm through the introduction of satellite data assimilation. Pre-existing wave energy resource assessment was found to underestimate the resource by up to 30%. Previously unidentified patterns of increased wave energy intensiveness found off the northwest coast of Ireland.